Importance of Local Climate Zones and Urban Heat Island study in Nepal - Thapa Chhetri, Deepak Bikram; Regmi, Pukar (Kathford Journal of Engineering and Management, 2023)
Various scientific research and literatures have documented the effect of urbanization on local climate. Urban rural temperature and humidity difference i.e. Urban Heat Island (UHI) and Urban Dry Island (UDI) respectively have been reported for cities and regions worldwide, mostly with local field sites that are extremely diverse in their physical and climatological characteristics. Generally, the UHI study relies on simplistic descriptors such as “urban” and “rural”. While these descriptors may be evocative of the landscape, they are insufficient in providing information like its site properties which have direct impacts on the surface layer climate. To fulfil the gap and for the clarity “local climate zone” (LCZ) classification is a very good tool. Each classification is unique in its combination of surface structure, cover, and human activity. The standard framework for each zone helps to classify an area for reporting and comparing field sites and their temperature observations. The LCZ not only helps in UHI and UDI study but also helps in planning smart environment and human friendly cities, landscape, and global climate change investigation. Nepal now being a federal state, many states having smart developmental drive of cities focusing only on physical infrastructure without considering UHI effect must incorporate study of cities by LCZ for sustainable urbanization.